The second jungle book Mowgli & Baloo - Johnson, Bayard; Horton, Matthew; McLachlan, Duncan, 1953-; Campbell, William, 1959-; McDowall, Roddy; Williams, Jamie; Kipling, Rudyard; MDP Worldwide; Columbia TriStar Home Video (Firm) (Culver City, CA : Columbia TriStar Home Video, 2003)
Pre-teen jungle boy Mowgli gets to human world and is pursued by P.T.Barnum circus scout Harrison who wants to take him to circus as curiosity. Harrison hires local grandee Buldeo for help in tracking Mowgli down. It turns out to be that Mowgli is Buldeo's nephew, and the only obstacle for him to take his late brother's rich estate.
Based upon Rudyard Kipling's The second jungle book : Kaa's hunting.
Originally released as a motion picture in 1997.
Some of the DVD packaging states DVD contains both widescreen and full screen versions on disc, but when watched there is only the full screen version.
Special features: bonus trailers; talent files.
Costume designer, Ann Hollowood ; edited by, Marcus Manton ; music composed by, John Scott ; production designer, Errol Kelly ; director of photography, Adolfo Bartoli.
Bill Campbell, Roddy McDowall, Jamie Williams, David Paul Francis, Gulshan Grover, Dyrk Ashton.
Keywords: Feature films; Films for the hearing impaired